좌굴과 상변화를 이용한 Micro Actuator의 개발 및 해석 - 송귀은; 김정식; 김광호; 이윤표 (대한기계학회, 2004)
A new micro actuation concept is introduced and studied in this paper. This idea is based on the thermo-pneumatic actuation principle. In order to improve the performance of a conventional thermo-pneumatic actuator, the idea of bistable buckling is added. By using a membrane which has the bistable buckling characteristics, the working pressure difference can be increased and as a result the work output can be increased. The analysis model for each phenomenon, bistable buckling and phase change, are suggested and the each model is verified with experimental data. From the comparison of the theoretical prediction with the experimental results, it can be concluded that these models are useful for such micro actuator analysis.